Evaluation of antioxidant and hepatoprotective effects of Khamira Gaozaban Ambri Jadwar Ood Saleeb Wala (KGA) - Muhammad Shoaib Akhtar; Hafiz Muhammad Mazher Asjad; Sajid Bashir; Abdul Malik; Rehan Khalid; Faisal Gulzar; Nadeem Irshad (Bangladesh Pharmacological Society, 2013)
Despite widespread use of Khamira Gaozaban Ambri Jadwar Ood Saleeb Wala (KGA) in the traditional medicine, there was a lack of scientific evidence on its efficacy and safety. The present investigation was designed to evaluate its ex vivo antioxidant and in vivo hepatoprotective properties against carbon tetrachloride toxicity in albino rats. At first phytochemicals analysis of test preparation was conducted to estimate its total phenolic and flavonoid contents. Then their antioxidant activity was determined by various tests and compared it with standards ascorbic acid and rutin. Afterwards, hepatoprotective activity was studied against carbon tetrachloride-induced liver damage by determining SGOT, SGPT, ALP, total cholesterol, bilirubin and total proteins contents in the serum of rats before and after treatment. This suggests that the hepatoprotective activity of formulation is possibly attributed to its free radical scavenging properties.